FIRST RECORD OF Thamnaconus modestoides (Barnard, 1927) (Tetraodontiformes: Monacanthidae) in Indonesia - Peristiwady, T. (Marine Research in Indonesia, 2009)
This paper gave evidence of the occurrence of Thamnaconus modestoides in Indonesian waters. A specimen (271.15 mm SL) was collected from the Winenet fish market at Bitung, North Sulawesi in March 2008. It was reported being caught in the depth of 20-30 m, in association with other coral-reef fishes, despite the fact that member of Thamnaconus has been known as deep water species. The morphological features of this new record species were discussed and illustrated.